2017
DOI: 10.1080/09599916.2017.1334222
|View full text |Cite
|
Sign up to set email alerts
|

The restructuring of the institutional real estate portfolio in the UK

Abstract: Real estate investment portfolios of financial institutions have seen dramatic changes over the last three decades or more. Historically such property investment decisions have been seen within a portfolio diversification paradigm that has sought to balance risk and return. This paper considers the role of the supply of assets in the determining and constraining the UK institutional portfolio. The supply of real estate assets not only expands during property booms but has also been transformed by a long term u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Indeed, many researchers have concluded that there is a premium for green-labeled buildings both in terms of rent and sales price (e.g., Dermisi, 2009;Wiley, Benefield, and Johnson, 2010;Das, Tidwell, and Ziobrowski, 2011;Gripne, Martel, and Lewandowski, 2012;Chegut, Eichholtz, and Kok, 2014;Das and Wiley, 2014;Fuerst and van de Wetering, 2015). In accordance with the workings and dynamics of the real estate market (see DiPasquale and Wheaton, 1992;Ball, Lizieri, and MacGregor, 1998;Dunse, Leishman, and Watkins, 2002;Roxana and Vasile, 2012;Jones, 2013), the existence of a green premium could potentially drive the investment and development of new green-labeled buildings, as well as the green-refurbishment of the existing uncertified buildings.…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…Indeed, many researchers have concluded that there is a premium for green-labeled buildings both in terms of rent and sales price (e.g., Dermisi, 2009;Wiley, Benefield, and Johnson, 2010;Das, Tidwell, and Ziobrowski, 2011;Gripne, Martel, and Lewandowski, 2012;Chegut, Eichholtz, and Kok, 2014;Das and Wiley, 2014;Fuerst and van de Wetering, 2015). In accordance with the workings and dynamics of the real estate market (see DiPasquale and Wheaton, 1992;Ball, Lizieri, and MacGregor, 1998;Dunse, Leishman, and Watkins, 2002;Roxana and Vasile, 2012;Jones, 2013), the existence of a green premium could potentially drive the investment and development of new green-labeled buildings, as well as the green-refurbishment of the existing uncertified buildings.…”
Section: Introductionmentioning
confidence: 92%
“…At the beginning of the process, the greenness of offices is a secondary demand characteristic subservient to location and the suitability/functionality of space (Jones, 2013). If and when the benefits of green offices to tenants become widely accepted, and such offices become the norm, then there could be a negative impact on the values of non-green stock.…”
Section: ͉ T H E G R E E N I N G P R O C E S Smentioning
confidence: 99%
See 3 more Smart Citations